ANALYSIS OF THE MEANING OF MASCULINITY IN BIRDS OF PREY - NAOMI S HUTABARAT; FLORI MARDIANI LUBIS; OKY OXCYGENTRI (INTERNATIONAL JOURNAL OF MULTI SCIENCE, 2020)
"Birds of Prey" is a DC-produced action adventure superhero film, adapted from DC Comics under a different title. The film tends to feature a representation of masculinity from Harley Quinn's character. Masculinity is usually attached to men, however, in this film it is aimed at women. The film is also a female-led film, the partner of batman's enemy Joker. Therefore, the author is interested in analyzing the film Birds of Prey so that the research is titled "Analysis of the Meaning of Masculinity in Birds of Prey". This research aims to find out the meaning of denotations, connotations and myths about masculinity presented in the film Birds of Prey played by Harley Quinn. This research is qualitatively descriptive using Roland Barthes's semiotic method. The results of this study are myths of masculinity in the film Birds of Prey presented by Harley Quinn through appearance, expression, behavior, environment, music, character and dialogue.